Review of codes of conduct, voluntary guidelines and principles relevant for farm data sharing - Wiseman, Leanne; Pesce, Valeria; Zampati, Foteini; Sullivan, Shawn; Addison, Chris; Drolet, Jacques (Technical Centre for Agricultural and Rural Cooperation, 2019)
Codes of conduct, voluntary guidelines, sets of principles on how to transparently govern farm data are a recent thing. While laws and regulations that govern personal data are becoming more and more common, legislation still does not cover data flows in many industries where different actors in the value chain need to share data and at the same time protect all involved from the risks of data sharing. Data in these value chains is currently governed through private data contracts or licensing agreements, which are normally very complex and on which data producers have very little negotiating power. Codes of conduct have started to emerge to fill the legislative void and to set common standards for data sharing contracts: codes provide principles that the signatories/subscribers/members agree to apply in their contracts.